TRIADIC DECODING OF THE CONCEPT OF LOGISTICS SERVICE: A THEORETICAL AND METHODOLOGICAL APPROACH - Fedotova, Iryna; Bocharova, Nadiia (Social Economics, 2025)
The article explores the conceptual foundations and strategic dimensions of logistics service management in the context of modern supply chain systems. Logistics service is viewed as a complex and dynamic system that integrates logistical operations, resource utilization, stakeholder interactions, and technological support to meet customer expectations and ensure competitiveness. The research is based on the triadic model of auxiliary concepts, allowing the synthesis of key categories such as logistics services, performers, resources, planning, execution, monitoring, customer satisfaction, flexibility, and strategic supply chain integration. These elements are grouped into synthesized concepts – integrated systems, management mechanisms, and results – providing a framework for understanding the holistic nature of logistics service management. Through this framework, the paper identifies six strategic schemes (A–F) that represent different approaches to logistics service management, including strategic management, service delivery, integration and adaptation, logistics service organization, corporate logistics management, and strategic logistics leadership. Each scheme highlights the interaction of specific triads that reflect the essence, mechanisms, and outcomes of logistics activities. The analysis reveals that effective logistics service management requires not only operational excellence but also strategic foresight, stakeholder engagement, sustainable resource use, and quality management practices. The article concludes that logistics service management is a core component of corporate governance, contributing to organizational resilience, customer value, and sustainable development. The proposed conceptual model provides a systematic basis for further academic research and practical improvement in logistics strategy, performance evaluation, and innovation.